O atendimento psicológico a crianças com problemas escolares: a queixa escolar nos prontuários de psicologia - Dias, Rogério (2008)
This present study aimed at investigating the procedures used and the explanations given regarding children that have been taken care of regarding school complaints in a psychological clinic-school in the Grande ABC area (SP) in 2005 and 2006. In order to reach this aim, one has researched some records of psychological attendance analysing the following variables: 1) to which sector the child with school complaint has been sent after the selection made by the person responsible for that; 2) the procedures adopted in psychological attendance that involve this kind of complaint and 3) the interpretations that were given regarding the school problems presented by these children. 26 records of children with school compaints have been found during the selected period. Amongst those documents, however, only nine were clear enough to show how the children were treated and to analyse the interpretations given to their complaints; other nine records belonged to individuals that gave up treatment after the selection interview or during treatment and eight records did not contain enough information in order to allow research according to the proposed aims. The results of this research point out to the direction that every child in the program, after a selection interview with the person in charge for that, has been directed to a certain center for psychological attendance in the institution. Regarding the procedures that were adopted during the attendances, there was the predominance of application of traditional evaluation tools and the contact with the schools where these children came from, when it happened, was by means of reports that were sent to the teaching institutions, but they only served to ratify the complaint that had been the reason to send children for treatment. Finally, the explanations regarding the problems presented by these children were centered on the questions of the individuals, privileging a subjectivist conception of problems. One can conclude that psychological knowledge and tools that have been applied in these attendances are used in an instrumental manner, or rather, they have an end in themselves and the interpretations given regarding the school complaints, reduced to psychologism, emphasizing the rupture between the individual and society. In order to offer support for the discussions presented in this research, one has used Critical Theory authors, especifically the studies of Theodor Adorno and Herbert Marcuse about technology, education and psychology